2019
DOI: 10.5194/tc-13-2733-2019
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting thinning patterns between lake- and land-terminating glaciers in the Bhutanese Himalaya

Abstract: Abstract. Despite the importance of glacial lake development in ice dynamics and glacier thinning, in situ and satellite-based measurements from lake-terminating glaciers are sparse in the Bhutanese Himalaya, where a number of proglacial lakes exist. We acquired in situ and satellite-based observations across lake- and land-terminating debris-covered glaciers in the Lunana region, Bhutanese Himalaya. A repeated differential global positioning system survey reveals that thickness change of the debris-covered ab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
90
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(92 citation statements)
references
References 78 publications
2
90
0
Order By: Relevance
“…Sustained glacier recession is driving the development of proglacial lakes at the termini of glaciers as meltwater accumulates within bedrock basins, behind moraine ridges and outwash fan heads, or is impounded by dead ice (Carrivick & Tweed, 2013). Glaciers in contact with a lake are receding more rapidly than their land‐terminating counterparts, for example, in the Himalaya (Maurer et al, 2019; Tsutaki et al, 2019), in Alaska (Larsen et al, 2007; Willis et al, 2012), and in New Zealand (Chinn et al, 2012). Glaciers terminating in proglacial lakes can lose mass by several mechanisms in addition to melt from energy exchanges at the ice surface, namely, calving and subaqueous melting, collectively known as frontal ablation (Maurer et al, 2016; Sakai et al, 2009; Truffer & Motyka, 2016; Watson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Sustained glacier recession is driving the development of proglacial lakes at the termini of glaciers as meltwater accumulates within bedrock basins, behind moraine ridges and outwash fan heads, or is impounded by dead ice (Carrivick & Tweed, 2013). Glaciers in contact with a lake are receding more rapidly than their land‐terminating counterparts, for example, in the Himalaya (Maurer et al, 2019; Tsutaki et al, 2019), in Alaska (Larsen et al, 2007; Willis et al, 2012), and in New Zealand (Chinn et al, 2012). Glaciers terminating in proglacial lakes can lose mass by several mechanisms in addition to melt from energy exchanges at the ice surface, namely, calving and subaqueous melting, collectively known as frontal ablation (Maurer et al, 2016; Sakai et al, 2009; Truffer & Motyka, 2016; Watson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Dehecq et al (2019) documented widespread land-terminating glacier slowdown since the start of the 21 st century across High Mountain Asia (HMA) in response to diminished driving stress caused by long-term ice thinning. In contrast, more localised studies have shown several examples of lake-terminating glacier flow acceleration over a similar time period (King et al, 2018;Liu et al, 2020;Song et al, 2017;Tsutaki et al, 2019). The number and total area of proglacial lakes in the Himalayan region has increased (Nie et al, 2017;Shugar et al, 2020;Zhang et al, 2015), a trend which is likely to continue in the near future, as many glaciers are situated within overdeepenings (Linsbauer et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Numerical ice-flow models have been utilised to investigate the dynamic thinning of marine-terminating outlet glaciers (Benn et al, 2007a;Enderlin et al, 2013;Nick & Oerlemans, 2006;Vieli et al, 2001;Vieli & Nick, 2011) and more recently of laketerminating glaciers in alpine regions (Sutherland et al, 2020;Tsutaki et al, 2019). Tsutaki et al (2019) employed a diagnostic 2-d model setup to show that the transition from a land to a lake-terminating boundary condition will significantly increase the surface flow velocities near the calving front. Sutherland et al (2020) used a numerical transient model setup to show that a proglacial lake was a dominant control on the ice velocity during times of glacial lake growth after the Last Glacial Maximum in New Zealand.…”
Section: Introductionmentioning
confidence: 99%
“…In order to better understand the impact of proglacial lakes onto glacier dynamics and to find out whether the contribution of lake-terminating glaciers to Himalayan ice mass loss may increase further, more multi-decadal analysis on the glacier-lake dynamics, such as done by Liu et al (2020), is needed. Also there is an urgent call for more modeling studies on glacier-lake dynamics like Tsutaki et al (2019) and such studies should address problems of varying complexity such as glacier flow responds onto a reduction of effective pressure or changes in basin width, or higher-order models addressing the importance of the longitudinal stress gradient. Ultimately, comprehensive transient models are needed that couple lake development, glacier dynamics and calving fluxes to make better predictions of near future ice loss of Himalaya glaciers.…”
Section: Implications For Future Evolution Of Himalayan Glaciersmentioning
confidence: 99%